Political Affairs in the Catholic News. Attitudes and Impulses of Active Readers - Rončáková, Terézia (Communication Today, 2025)
The article continues in the research of presidential elections 2014 in the Church media. The author is asking, how the identified state is perceived by readers of the weekly Catholic news. This research problem is solved by the quantitative – qualitative questionnaire method oriented on active readers. The author analyses the results at two levels: firstly, the readers were asked to evaluate the election supplement; secondly, they evaluated general doing of the newspaper in connection with all election forms. She offers her conclusions related to attitudes of the readers dependent of their age, education, readers’ and electors’ activity. She also notes that the active readers who are more unsatisfied with the present state (concretely with the supplement and specifically with the approach to the elections) are mostly men, younger and more educated people, and city dwellers. These are calling for competent opinion genres (analyses and columns, including columns written by Church authorities) and for bigger courage, openness and directness of the editorial team. In the context of previous foreign and domestic researches, the author points out the existence of space for an opinion-making, socially active Church medium that is able to fully accept the concrete and unequivocal character of journalistic style of expression in order to attract the attention of younger members of potential audiences.